2014
DOI: 10.1002/adma.201306136
|View full text |Cite
|
Sign up to set email alerts
|

All Spraying Processes for the Fabrication of Robust, Self‐Healing, Superhydrophobic Coatings

Abstract: The spraying method is developed for the fabrication of mechanically robust and self-healing superhydrophobic coatings, which comprise highly porous and rough polyelectrolyte coatings preserved with low-surface-energy healing agents. These coatings can repetitively and autonomically restore superhydrophobicity in humid environments. After depletion of healing agents, superhydrophobic coatings with dual healing agents can regain their self-healing ability by re-spraying fluoroalkylsilane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
203
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(205 citation statements)
references
References 33 publications
1
203
0
1
Order By: Relevance
“…55 The molecular self-assembly has been reported in numerous research papers. 20,7684 It may be achieved in different manners, such as solution immersion process, 16,24,82 roomtemperature vacuum approach, 81 chemical vapor deposition, 20 spraying process, 77 flame spray pyrolysis, 83 and so on. For example, Lu et al reported a cost-effective method to fabricate a graphene-modified foam via the convenient thermal reduction process of graphene oxide along with the reduced graphene's self-assembly.…”
Section: The Coating Methodmentioning
confidence: 99%
See 2 more Smart Citations
“…55 The molecular self-assembly has been reported in numerous research papers. 20,7684 It may be achieved in different manners, such as solution immersion process, 16,24,82 roomtemperature vacuum approach, 81 chemical vapor deposition, 20 spraying process, 77 flame spray pyrolysis, 83 and so on. For example, Lu et al reported a cost-effective method to fabricate a graphene-modified foam via the convenient thermal reduction process of graphene oxide along with the reduced graphene's self-assembly.…”
Section: The Coating Methodmentioning
confidence: 99%
“…Sun et al fabricated self-healing, robust, and superhydrophobic coatings on fabrics through all spraying layer-by-layer (LbL) assembly process. 77 In this study, the LbL assembly process was conducted by subsequently spraying three polyelectrolyte complexes, namely poly(allylamine hydrochloride), sulfonated poly(ether ether ketone) (PAHSPEEK), and poly(acrylic acid) (PAA) to form high porous and rough coatings with nanostructures satisfying the need of superhydrophobicity. Taking the advantage of positively charged poly(diallyldimethylammonium chloride) (PDDA) to strengthen their adhesion toward coatings, this superhydrophobic coating also has self-healing ability.…”
Section: The Coating Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, self-healing abilities can be introduced into superhydrophobic coatings to enable the repair of the damaged surface chemistry and/or morphology, which can significantly extend their service lives [15][16][17] . For example, inorganic/organic micro-/nanocontainers have been used in superhydrophobic coatings for storing low-surface-energy materials [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Li et al fabricated a self-healing superhydrophobic coating by spraying layer-by-layer (LbL) assembly of poly(allylamine hydrochloride)-sulfonated poly(ether ether ketone), poly(acrylic acid) and healing agents, such as peruorooctanesulfonic acid lithium salt (PFOS) or uoroalkyl silane (POTS), on the surfaces of substrates. 20 When the surface of this polyelectrolyte coating was damaged, the stored POTS or PFOS in the coating could migrate to the damaged surface for healing the wettability under a minor humid condition. Esteves et al reported a selfreplenishing superhydrophobic coating consisting of a dispersion consisting of dual-sized silica nanoparticles and uoroalkyl-terminated polymeric dangling chains.…”
Section: Introductionmentioning
confidence: 99%